FOOD PRACTICES IN CHILDREN FROM ZERO TO TWO YEARS OLD ADMITTED TO A UNIVERSITY HOSPITAL OF SOUTHERN BRAZIL - Ana Paula Reyes da Silva; Fernanda Barbosa Bernardes; Juliane Alves Santos; Natália Machado de Miranda; Marianna Sperb; Ester Zoche; Vera Lúcia Bosa (Universidade do Estado do Rio de Janeiro, 2019)
Objective: To identify and describe the eating practices of children from zero to two years of age admitted to a university hospital in Porto Alegre-RS. Methods: The dietary practices of 261 children were identified by an instrument composed of questions that analyze attributes, components and markers of complementary feeding. The variables were expressed as percentage and absolute value, mean and standard deviation or median and interquartile range. Results: Exclusive breastfeeding up to six months was present in 25.3% of the sample, with a median duration of 45 days, and the introduction of complementary feeding was started at an appropriate time (six to seven months) in 57%. Among children who had already started complementary feeding through fruit porridge or main meal (n= 128), the median age of introduction was 5 (4-6) months. Regarding adequacy, food sources of vitamin A and iron were present in 83.6% of the children, and 62.5% consumed all food groups. Consistency of food was adequate in 52.3%. The consumption of ultra-processed foods was present in the diet of 60.2% of the children. Conclusions: Low prevalence of exclusive breastfeeding, early introduction of complementary feeding and high frequency of ultra-processed foods were observed. The identified improper eating practices can compromise the health of the child, and it is important to take actions to promote breastfeeding and the adequate introduction of complementary feeding. DOI: 10.12957/demetra.2019.43304